The Comparison of Food and Nutrient Intake among Iranian Diabetic and Non-Diabetic Adults - Najmeh Maayeshi; Hassan Mozaffari-Khosravi; Sayyed Saeid Khayyatzadeh; Hossein Fallahzadeh (Journal of Nutrition and Food Security)
Background: Diabetes is known as a rising global health metabolic disorder. Eating choices are considered as a main factor in type 2 diabetes (T2D) prevention and treatment. This study aimed to investigate the comparison of food and nutrient intake among diabetic and non-diabetic adults in Iran. Methods: This cross-sectional study was performed on 5442 Iranian adults aged 35–70 years from Shahedieh cohort study, Yazd, Iran. Dietary intake of participants was evaluated using a validated 121-item food frequency questionnaire. All data about the amount of food groups, total energy, micronutrients, and macronutrients intake were analyzed using SPSS version 23.0. Results: Participants without diabetes showed significantly higher intake of grains, legumes, total meat, fats, sweets, energy, carbohydrates, total fat, total cholesterol, saturated fatty acids, monounsaturated fatty acids, polyunsaturated fatty acids, vitamin B9, B12, A, and D in comparison with patients with diabetes. On the other hand, diabetic patients revealed significantly higher amounts of vegetables, fruits, dietary fiber, biotin, potassium, and magnesium consumption compared to non-diabetic participants. Conclusion: Given that diet and nutrition are widely believed to play an important part in the development of T2D, significant differences were found in dietary habits of diabetic patients in comparison with participants without diabetes. These findings suggest that emphasis on education is required to improve the current dietary behaviors to assist in the prevention of  disease complications.